2021
DOI: 10.1186/s40529-021-00317-6
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific competition in germination of bird-dispersed seeds in a habitat with sparse tree vegetation in South Africa

Abstract: Background By transporting and scarifying the seeds during ingestion, avian frugivores reduce the competition with siblings, and may improve the germination which is critical for dispersal effectiveness and population recruitment. However, generally, there is limited knowledge on how deposited seeds interact/compete in the new microsite. We tested the hypothesis that the bird-dispersed seeds benefit from improved germination after their passage through the bird’s gut; and we investigated the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 99 publications
(148 reference statements)
1
16
0
1
Order By: Relevance
“…In the same manner, this study indicates unchanged O. europaea subsp. africana seed germination after passing through bird guts has been previously reported by Vukeya et al (2021). It is a likely result of possible frugivorous bird gut adaptations to the egestion of indigestible fruit material such as seeds (Jordano, 2000;Mokotjomela et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the same manner, this study indicates unchanged O. europaea subsp. africana seed germination after passing through bird guts has been previously reported by Vukeya et al (2021). It is a likely result of possible frugivorous bird gut adaptations to the egestion of indigestible fruit material such as seeds (Jordano, 2000;Mokotjomela et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
“…We found that the seeds of O. europaea subsp. africana germinated at a slower rate (up to 33 weeks), possibly because of the high resistance of their seed coat to scarification, within the gut of the vertebrates, to early release of seed dormancy (Mokotjomela, 2012;Vukeya et al, 2021Vukeya et al, , 2022. Slow germination might retard recruitment since Schupp (1993) argued that of utmost importance in the TA B L E 1 Potential seed dispersal effectiveness for the two groups of organisms that influenced recruitment processes in O. subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we argue that the observed changes in vegetation cover, which indicate an increase in woody species' cover between 1987 and 2017, can be partly attributed to the substantial seed rain associated with resident frugivorous bird species and colonial wintering birds (Vukeya et al 2020;Vukeya et al 2022). It has been shown that bird species' gut treatment of the seeds promotes the germination of the local woody plant species (Mokotjomela et al 2021;Vukeya et al 2021). Woody cover encroachment reportedly jeopardises grassland biodiversity and transforms grasslands and savannas into shrublands and woodlands (Archer et al 2001(Archer et al , 2017.…”
Section: Detecting Vegetation Cover Changementioning
confidence: 97%
“…Seed dispersal is important for reducing competition among siblings, species' colonisation of new sites, gene mixing and population persistence (Clark et al, 1999; Howe & Smallwood, 1982; Nathan et al, 2003). The phenology of seed dispersal is critical to the successful recruitment of species (Jordano, 2000; Stiles, 1980), since dispersed seeds require conducive conditions for germination (Footitt et al, 2018; Vukeya et al, 2021); and where dispersal vectors are migratory, fruit ripening and the arrival of the vectors should be synchronised (Johnson et al, 2019; Stiles, 1980). Phenology is a study of the timing of reproductive biological events (e.g.…”
Section: Introductionmentioning
confidence: 99%